2020
DOI: 10.1186/s13047-020-00426-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations of foot and ankle characteristics with knee symptoms and function in individuals with patellofemoral osteoarthritis

Abstract: Background Foot and ankle characteristics are associated with patellofemoral pain (PFP) and may also relate to patellofemoral osteoarthritis (PFOA). A greater understanding of these characteristics and PFOA, could help to identify effective targeted treatments. Objectives To determine whether foot and ankle characteristics are associated with knee symptoms and function in individuals with PFOA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…Therapeutic exercise in physiotherapy is effective in seven studies (Tan et al, 2020;Nielsen et al, 2020;Chang et al, 2015;Lee et al, 2021;Faisal Chevidikunnan et al, 2016;de Oliveira Silva et al, 2019) which all the results show consistent findings with Willy et al, (2019). It is agreeable that therapeutic exercises can improve muscle strength and reduce pain in PFPS.…”
Section: Therapeutic Exercisesmentioning
confidence: 56%
See 3 more Smart Citations
“…Therapeutic exercise in physiotherapy is effective in seven studies (Tan et al, 2020;Nielsen et al, 2020;Chang et al, 2015;Lee et al, 2021;Faisal Chevidikunnan et al, 2016;de Oliveira Silva et al, 2019) which all the results show consistent findings with Willy et al, (2019). It is agreeable that therapeutic exercises can improve muscle strength and reduce pain in PFPS.…”
Section: Therapeutic Exercisesmentioning
confidence: 56%
“…2.1 Physiotherapy management 2.1.1 Therapeutic Exercise in the Rehabilitation of PFPS Tan et al (2020) found that decreased weight-bearing ankle dorsiflexion range increased knee pain, Anterior Knee Pain Score (AKPS), and maximum knee pain during stair ambulation, worsening disability. Although minor, higher Foot Posture Index (FPI) scores imply overly pronated foot posture and midfoot mobility connected to fewer single step-ups and double-leg sit-to-stands to knee discomfort.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A variação nas respostas individuais sublinha a necessidade de estratégias terapêuticas adaptativas e individualizadas para otimizar a amplitude de movimento. Tan et al (2020), ao analisar características específicas do pé e do tornozelo em relação a sintomas e função do joelho, destaca a modesta explicação da variação na dor e incapacidade no joelho por essas características. Este resultado sugere que, embora importantes, as características do pé e tornozelo podem explicar apenas uma fração da complexidade envolvida nas disfunções articulares relacionadas ao joelho.…”
Section: Fonte: Autoria Própria (2023)unclassified